Selective use of pancreatic duct occlusion during pancreaticoduodenectomy in patients with a small-size duct and atrophic parenchyma in the distal pancreas: A retrospective study - Chen, Guangbin; Yin, Jie; Chen, Qun; Wei, Jishu; Zhang, Kai; Meng, Lingdong; Lu, Yichao; Wu, Pengfei; Cai, Baobao; Lu, Zipeng; Miao, Yi; Jiang, Kuirong (Frontiers in Surgery, 2023)
Background: Despite advancements in surgical techniques, postoperative pancreatic fistula (POPF) remains a potentially life-threatening complication of pancreaticoduodenectomy (PD). Pancreatic duct occlusion (PDO) without anastomosis has been proposed to alleviate the clinical consequences of POPF in selected patients after PD. Objectives: To assess the safety and effectiveness of PDO with mechanical closure after PD in patients with an atrophic pancreatic body-tail and a small pancreatic duct. Methods: From April 2019 to October 2020, we retrospectively identified two female and two male patients by preoperative computed tomography of the abdomen. Three patients underwent PDO with mechanical closure after PD and one underwent PDO after pylorus-preserving pancreaticoduodenectomy. Patients’ medical records and medium-term and long-term follow-up data were analyzed. Results: The postoperative histological examination revealed solid pseudopapillary tumor in two patients, pancreatic ductal adenocarcinoma in one patient, and chronic pancreatitis with pancreatic duct stones in one patient. None of the patients developed biochemical or clinically relevant POPF, with no postpancreatectomy hemorrhage, biliary leakage, delayed gastric emptying, intra-abdominal abscess, or chyle leakage noted. Among the four patients, three developed new-onset diabetes mellitus and one had impaired glucose tolerance. Three patients received pancreatic enzyme supplementation at a dose of 90,000 Ph. Eur. units/d, and one patient was prescribed a higher dose (120,000 Ph. Eur. units/d). Conclusions: PDO with mechanical closure is an alternative approach for patients with an atrophic pancreatic body-tail and a small pancreatic duct after PD. Further evidence is required to evaluate the potential benefits of selective PDO in these patients.